Interstellar scintillation, ISS, and intrinsic variability of radio AGN. Issue 2 (15th January 2020) - Jauncey, David L.; Koay, Jun Yi; Bignall, Hayley; Macquart, Jean-Pierre; Pursimo, Tapio; Giroletti, Marcello; Hovatta, Talvikki; Kiehlmann, Sebastian; Rickett, Barney; Readhead, Anthony; Max-Moerbeck, Walter; Vedantham, Harish; et al.
Abstract: We investigate the relationship between the 5 GHz interstellar scintillation (ISS) and the 15 GHz intrinsic variability of the compact, radio-selected active galactic nuclei (AGN) common to the Microarcsecond Scintillation-Induced Variability (MASIV) Survey and the Owens Valley Radio Observatory blazar flux density monitoring program. As part of this investigation, we also re-examine the reported intrinsic nature of the February 1990 VLA observations of the blazar S5 0716+714. We are also examining the presence of IDV/ISS in the Owens Valley 15 GHz flux density monitoring data. We find a significant relationship between the Owens Valley 15 GHz modulation index and the MASIV modulation index. We also discuss the implications of these findings for RadioAstron.